2016
DOI: 10.1080/1343943x.2015.1128088
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of high yield under cluster planting: photosynthesis and canopy microclimate of cotton

Abstract: a linze inland river Basin research Station/Heihe Key laboratory of ecohydrology and integrated river Basin Science, cold and arid regions environmental and engineering research institute, chinese academy of Sciences, lanzhou, china; b linze inland river Basin research Station/ Key laboratory of land Surface Process and climate change in cold and arid regions, cold and arid regions environmental and engineering research institute, chinese academy of Sciences, lanzhou, china; c School of life Sciences, lanzhou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…The lowest value was obtained at a 10 cm plant spacing, while the highest value was obtained in the no thinning application. Xie et al (2016) reported that canopy temperature decreased with increased plant density, which differed from the present findings. This may have been due to differences in climate, temperature, humidity, leaf/canopy temperature measurements and irrigation.…”
Section: Bednarzcontrasting
confidence: 99%
See 1 more Smart Citation
“…The lowest value was obtained at a 10 cm plant spacing, while the highest value was obtained in the no thinning application. Xie et al (2016) reported that canopy temperature decreased with increased plant density, which differed from the present findings. This may have been due to differences in climate, temperature, humidity, leaf/canopy temperature measurements and irrigation.…”
Section: Bednarzcontrasting
confidence: 99%
“…The highest chlorophyll content was obtained in the no thinning application (43.75), and the lowest value was obtained at a 15 cm plant spacing (41.25). While the findings were in agreement with Janat and Khalout (2011), who reported that the chlorophyll content in the leaf was not influenced by plant density, Xie et al (2016) obtained different results.…”
Section: Bednarzsupporting
confidence: 90%
“…However, at the canopy level, higher LAI is directly associated with higher density of crop stands. Generally, denser canopies are characterized by more efficient light interception, higher relative humidity and lower temperature (Xie et al., ), thus reducing VPD within these canopies. As VPD is the major driver for transpiration (Farquhar & Sharkey, ), the comparably higher LAI on plots fertilized with K effectively moderated ET without affecting g s .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, with the increase in population, the arable land area for cotton production has gradually decreased, and cotton grain competition has become increasingly significant [8], resulting in a downward trend of cotton production overall. Cotton production is a group production under field conditions, and the yield per unit area mainly depends on the photosynthetic capacity of the population per unit area [9]. Therefore, the establishment of a population structure with high light efficiency is a core issue in the cultivation of high-quality and high-yield cotton.…”
Section: Introductionmentioning
confidence: 99%